2020
DOI: 10.30561/sinopusd.699738
|View full text |Cite
|
Sign up to set email alerts
|

Siniflarinda Farkli Kültürden Çocuk Olan Okul Öncesi̇ Öğretmenleri̇ni̇n Uyguladiklari Eği̇ti̇m Programina İli̇şki̇n Görüşleri̇ni̇n İncelenmesi̇

Abstract: Bu araştırmanın amacı, sınıflarında 48-72 aylık farklı kültürden çocuk bulunan okul öncesi öğretmenlerinin eğitim programındaki uygulamalarının incelenmesidir. Bu amaç doğrultusunda çalışma, nitel araştırma yöntemlerinden durum çalışması biçiminde desenlenmiştir. 2018-2019 eğitim-öğretim yılı bahar yarıyılında gerçekleştirilen bu araştırmanın çalışma grubunu, sınıfında farklı kültürden çocuk bulunan 13 okul öncesi öğretmeni oluşturmaktadır. Veri toplama aracı olarak, araştırmacılar tarafından geliştirilen yarı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
(6 reference statements)
0
3
0
2
Order By: Relevance
“…It was concluded that the teachers did not make arrangements in their plans for children from different cultural backgrounds. Alabay & Ersal (2020) state that this may be due to the fact that teachers' knowledge and skills about children from different cultural backgrounds are not adequate in the classroom. Sağlam & Kanbur (2017) stated in their study that they analyzed teacher attitudes towards refugee children, that they found it more appropriate not to make any changes in the plan.…”
Section: 2discussion On the Elements Of Multiculturalism In The Classroom Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It was concluded that the teachers did not make arrangements in their plans for children from different cultural backgrounds. Alabay & Ersal (2020) state that this may be due to the fact that teachers' knowledge and skills about children from different cultural backgrounds are not adequate in the classroom. Sağlam & Kanbur (2017) stated in their study that they analyzed teacher attitudes towards refugee children, that they found it more appropriate not to make any changes in the plan.…”
Section: 2discussion On the Elements Of Multiculturalism In The Classroom Environmentmentioning
confidence: 99%
“…When the literature on the subject in Turkey is analyzed, it is possible to come across studies on teachers' perceptions and practices of multiculturalism and its components. These studies generally examine preschool teachers' perceptions and attitudes towards multiculturalism (Akkaya, Sahin & Gezer Sen, 2021;Alabay & Ersal, 2020;Mazı, 2018;Özözen Danacı, Eran, Çetin, Pınarcık, & Bahtiyar, 2016;Mazı, 2018;Pekdoğan, 2018;Taştekin, Bozkurt Yukcu, Izoglu, Gungor). , Işık Uslu & Demircioğlu, 2016) Alabay & Ersal (2020), as a result of their interviews with the teachers of preschool children from different cultural backgrounds, revealed that the teachers did not make any arrangements for these children in their plans, classroom environments and family participation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Çocuklar dil farklılıklarında dolayı özellikle eğitim hayatında büyük zorluklarla karşılaşmaktadır. Bu sorun sadece Türkiye' de değil dünyada göç alan birçok ülkenin genel sorunudur (Alabay ve Ersal, 2020;Goodwin, 2017;Kirmayer ve diğerleri, 2011). Amerika Birleşik Devletleri' nde yapılan çalışmalarda Latin Amerika'dan gelen geçici koruma altındaki çocukların alıcı ve ifade edici dil becerilerinin, geçici koruma altında olmayan çocukların dil becerilerine göre daha az gelişmiş olduğu görülmüştür (Halle ve diğerleri 2009;Klein, Aikens, West, Lukashanets ve Tarullo, 2013).…”
Section: Sonuç Ve Tartışmaunclassified
“…Olaylar, olgular ve durumlar hakkındaki ortak noktaları ya da farklılıkları belirler (Alabay, 2017).…”
Section: Introductionunclassified